2017
DOI: 10.3389/fpls.2017.01489
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Surface Charge and Functional Groups on the Adsorption and Binding Forms of Cu and Cd on Roots of indica and japonica Rice Cultivars

Abstract: This work was designed to understand the mechanisms of adsorption of copper (Cu) and cadmium (Cd) on roots of indica and japonica varieties of rice. Six varieties each of indica and japonica rice were grown in hydroponics and the chemical properties of the root surface were analyzed, including surface charges and functional groups (-COO- groups) as measured by the streaming potential and attenuated total reflectance-Fourier transform infrared spectroscopy (ATR-FTIR). Binding forms of heavy metals adsorbed on r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…Lowering pH increases the concentration of cationic species, whereas increasing pH tends to decrease cationic species and increase anionic species. However, changes of solution pH also affect the protonation status of functional groups on the cell wall (Liu et al 2017), and then the binding of metals to the cell wall becomes complex and highly dependent on the value of pH.…”
Section: Discussionmentioning
confidence: 99%
“…Lowering pH increases the concentration of cationic species, whereas increasing pH tends to decrease cationic species and increase anionic species. However, changes of solution pH also affect the protonation status of functional groups on the cell wall (Liu et al 2017), and then the binding of metals to the cell wall becomes complex and highly dependent on the value of pH.…”
Section: Discussionmentioning
confidence: 99%
“…Ion exchange and chemical complexation with functional groups on root surfaces are the main mechanisms controlling metal ions adsorption by plant roots. 12,13 The exchangeable Mn(II) of plant roots is active and the complexed Mn(II) is inactive as a result of complexation with the functional groups on the surfaces of various plant roots. Thus, the former can be taken up into plant roots, whereas the latter is not easy to be absorbed by the same plant roots.…”
Section: Discussionmentioning
confidence: 99%
“…11 The formation of complexes between ions and functional groups on the plant roots is an important mechanism for the adsorption of metal ions by plant roots. 12,13 It has been reported that ion exchange on plant roots is closely related to uronic acid levels in the cell walls of plant roots. 14 The adsorption of metal ions by the cell walls and membranes of plant roots and its effect on toxicity and the uptake of these metals has been extensively studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intensity of absorption peak in the spectrum represents the number of functional groups. As shown in Figure 3, the gradual peaks at 3,400, 1,635, 1,543, 1,247, and 1,031 cm −1 can be attributed to the polysaccharides (-OH stretching vibration), amide I (antisymmetric stretching vibrations of carboxyl), amide II (N-H bending vibrations), amide III (C-N stretching and N-H bending vibrations), and hemicelluloses (C-OH bending vibrations) (Xu et al, 2015;Liu et al, 2017;Ren et al, 2020). Under Al treatment, the intensity of characteristic peaks on the cell walls of both genotypes was significantly increased, indicating that Al induced the increase in the number of functional groups on the cell walls.…”
Section: Snp Regulated the Functional Groups Of The Cell Wall In Rice...mentioning
confidence: 97%